-4p=12

Simple and best practice solution for -4p=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4p=12 equation:


Simplifying
-4p = 12

Solving
-4p = 12

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Divide each side by '-4'.
p = -3

Simplifying
p = -3

See similar equations:

| a+8=a-3 | | 5(10x-10)=-5(-4x+14) | | t+-4t=-11 | | 3x+1.5=y | | 2s+q-5=x+5 | | 9p+4=9p-4 | | 8=4(2x+6) | | 2s+q-5=s+5 | | 12x^2=16x+1 | | 2x+5=6x-1 | | 3(x-4)+1=10 | | 75=3 | | 8n^2+6n=-5 | | 6-3y=4-4y | | 2x+6(x-2)=4x+12 | | 6(2x+8)-9x= | | X=35-2y | | 5r-15=4 | | h/3=-6 | | p+p+24+2p-29=583 | | h/3=6 | | (2x-3)=(x+12) | | 3g+3=-5(3-g) | | 16p-4=4(4p-3) | | 2+0.5x-2=8 | | 2x-5+4x=31 | | 5x-12=6x+5 | | 2.5(x-2)+4.5+1.5(x-3)=15 | | 2lx+1l-1=3 | | 3(2+8)=7z | | 2a=1.6a | | 3(x-3)=(x-1)+7 |

Equations solver categories